O-024 Core lab assessed real-life experience with the?embotrap thrombectomy device in the first?166 patients. (23rd July 2017) - Brouwer, P
Abstract : The Karolinska University Hospital is performing intra-arterial stroke treatment since 2006. We analyzed the radiological and clinical outcome of the first 166 patients that were treated using the Embotrap device. The patient group included all strokes, including those in the posterior fossa, as well as patients in all age groups. Since the operators were both experienced and inexperienced operators (supervised fellows), we consider this the 'real-life situation'. All clinical outcome measures were assessed by independent observers and a core-lab assessed the radiological outcome. Disclosures: P. Brouwer: 2; C; Neuravi Ltd., Codman DePuy-Synthes, Stryker, Medtronic, Balt extrusion. 4; C; Neuravi Ltd.